2016
DOI: 10.1016/j.quascirev.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Middle Pleistocene vertebrate fossils from the Nefud Desert, Saudi Arabia: Implications for biogeography and palaeoecology

Abstract: The current paucity of Pleistocene vertebrate records from the Arabian Peninsula-a landmass of over 3 million km 2-is a significant gap in our knowledge of the Quaternary. Such data are critical lines of contextual evidence for considering animal and hominin dispersals between Africa and Eurasia generally, and hominin palaeoecology in the Pleistocene landscapes of the Arabian interior specifically. Here, we describe an important contribution to the record and report stratigraphically-constrained fossils of mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 106 publications
6
65
0
Order By: Relevance
“…The upper three samples collected from JB3 had some of the greatest recorded carbonate contents, but also yielded uranium contents <2.5 ppm. This is more in line with typical uranium concentrations measured in the Nefud, which tend to be ≤3 ppm (Richard P Jennings et al, 2016;Rosenberg et al, 2013;Stimpson et al, 2016).…”
Section: Accepted Manuscriptsupporting
confidence: 82%
See 1 more Smart Citation
“…The upper three samples collected from JB3 had some of the greatest recorded carbonate contents, but also yielded uranium contents <2.5 ppm. This is more in line with typical uranium concentrations measured in the Nefud, which tend to be ≤3 ppm (Richard P Jennings et al, 2016;Rosenberg et al, 2013;Stimpson et al, 2016).…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…Numerous recent studies focusing on the Arabian Peninsula have provided chronologically secure data for key archaeological (Armitage et al, 2011;Groucutt and Petraglia, 2012;Groucutt et al, 2015b;Richard P. Jennings et al, 2016;Petraglia et al, 2015), palaeontological (Stimpson et al, 2016), and palaeoecological and palaeoclimatic applications (Parton et al, 2015a;Rosenberg et al, 2013Rosenberg et al, , 2011a. From these data, it is clear that multiple regions in the Arabian Peninsula have been considerably more humid in the past, with significant implications for biogeographical responses and population expansions into and through this region.…”
Section: Introductionmentioning
confidence: 99%
“…Allen's viewpoint was rapidly accepted in both the ecological and evolutionary research communities and since that time few authors have considered the African wolf a distinct species, despite there being a few notable exceptions: Keimer mentions C. lupaster in his faunal work on Egypt [45]; Kurtén lists the wolf jackal (C. lupaster) for a fossil collection from the Levant and suggests the presence of extant C. lupaster in North Africa [46]; Ferguson studied C. lupaster crania from Israel and concluded that C. aureus lupaster differs from C. aureus and represents a small desert race of C. lupus [38]. Most recently an m1 from Middle Pleistocene deposits in the Nefud Desert, Saudi Arabia, has been identified as C. anthus [47].…”
Section: History Of the African Wolfmentioning
confidence: 99%
“…The presence of lesser kudu in Saudi Arabia therefore raises the question whether they arrived during the Pleistocene and survived the Last Glacial Maximum in small refugia, yet in large enough numbers to sustain populations over some millennia. Alternatively, a dispersal of kudu during the Holocene humid period via the Sinai and Levant or the Red Sea is a possibility, as has been surmised for Middle and Late Pleistocene movements of other species (Breeze et al., ; Stimpson et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of palaeolakes is well attested at the oasis of Jubbah, with various lake phases dated to the early and middle Holocene, and palaeoecological reconstructions indicating well-vegetated environments Hilbert et al, 2014). Kudu are almost exclusively browsers (Estes, 1991;Kingdon, 1997); therefore, there must have Stimpson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%